Voice abnormalities and their relation with motor dysfunction in Parkinson's disease - MİDİ, İPEK (WILEY, 2008)
Objective To evaluate changes in perceptual and several acoustic parameters of voice in patients with Parkinson's disease (PD ) and to find out any relation with these parameters and motor components of Unified Parkinson's Disease Rating Scale (UPDRS) in this patient group. Materials and methods Twenty patients with PD (12 male and 8 female) were given objective and subjective voice tests and results were compared with those of 20 age- and sex-matched controls. Patient's perceptual voice analysis was assessed using GRBAS scale including Grade of Dysphonia, Roughness, Breathiness, Asthenia and Strain items. Measurements for objective voice analysis, acoustic assessment tests including frequency perturbation [jitter (jitt)%], intensity perturbation [shimmer (shim)%], noise to harmonic ratio (NHR), fundamental frequency (F0), variability of fundamental frequency (vF0), diadochokinetic rate (DDK) and maximum phonation time (MPT) were used. An assessment of disability caused by voice disorders was scored according to the Voice Handicap Index (VHI) by the patient. All subjects also underwent videolaryngostroboscopic (VLS) examination. Motor components of UPDRS and acoustic parameters of voice were investigated for any correlations. Results Compared with controls, roughness (P = 0.15), breathiness (P = 0.004) and asthenia (P = 0.031) values of males and breathiness (P = 0.043) and asthenia (P = 0.023) values of females were higher in patients with PD. Mean VHI scores of patients with PD were higher for both male and female patients (P = 0.0001 for male, P = 0.002 for female). The mean values for MPT (P = 0.02) and DDK (P = 0.025) were shorter in patients with PD. Jitt%, shim% and mean F0 values were similar among the two groups. But mean vF0 values were significantly higher in male patients with PD (P = 0.05). On VLS examination, non-closure glottic pattern was found to be more frequent in the PD group. Conclusion Although it is well known that pathophysiological changes in PD affect the voice, the present study found only few significant correlations between motor component of UPDRS and voice parameters.
Keywords: Parkinson's disease; voice analysis; Unified Parkinson's Disease Rating Scale; SPEECH; LEVODOPA